2013
DOI: 10.1161/circoutcomes.111.000041
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of Cardiopulmonary Resuscitation Quality on Cardiac Arrest Outcome

Abstract: Background-Evidence has accrued that cardiopulmonary resuscitation quality affects cardiac arrest outcome. However, the relative contributions of chest compression components (such as rate and depth) to successful resuscitation remain unclear.Methods and Results-We sought to measure the effect of cardiopulmonary resuscitation quality on cardiac arrest outcome through systematic review and meta-analysis. We searched for any clinical study assessing cardiopulmonary resuscitation performance on adult cardiac arre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 46 publications
(114 reference statements)
4
70
0
1
Order By: Relevance
“…Chest compression depth is an important component of CPR and should be measured routinely [19,20], the most effective depth is currently unknown. In our study, we obtained mean CC depth on 49.7 ± 8.4 mm.…”
Section: Both European and American Guidelines For Resuscitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chest compression depth is an important component of CPR and should be measured routinely [19,20], the most effective depth is currently unknown. In our study, we obtained mean CC depth on 49.7 ± 8.4 mm.…”
Section: Both European and American Guidelines For Resuscitationmentioning
confidence: 99%
“…In case of the CC rate recommended in ERC guidelines, ROSC was observed in 29%. Moreover, Wallace et al [20] presented a meta-analysis which stressed that CC rates closer to 85-100 cpm are significantly associated with improved survival from cardiac arrest. In our study the participants performed CCs according to international resuscitation guidelines (113.7 ± 14.2/min).…”
Section: Both European and American Guidelines For Resuscitationmentioning
confidence: 99%
“…For healthcare professionals, the quality of CPR delivered is critical because poor compliance with recommended guidelines has been associated with lower survival. 116,117 Suboptimal CPR harms patients 118 and is preventable. 119 Quality improvement processes are needed to try to minimize its occurrence.…”
Section: Basic Life Support Trainingmentioning
confidence: 99%
“…[10][11][12][13][14] A metaanalysis by Wallace et al found that survival was improved with chest compression depths of at least 51 mm and compression rates between 85 and 100 compressions per minute. 14 Vadeboncoeur et al conducted an observational study examining the influence of an educational intervention on high quality CPR and its impact on neurologically intact survival from OHCA and found that chest compressions with a depth of at least 51 mm were independently associated with survival from cardiac arrest with a favourable neurologic outcome. 13 …”
Section: Compression Rate and Depthmentioning
confidence: 99%